Assessing the AD8232 sensor's effectiveness on telemedicine kits: checking the AD8232 sensor (Research, Society and Development, 2022)
In pandemic times or due to patient’s motor disabilities, the visit to health care centers can be difficult. Fortunately, multiple solutions have emerged in the last decades to provide remote medical care. In this scenario, the monitoring of vital signals is crucial for a number of diseases. Technologies of Internet of Things (IoT) are improving the collection, digitalization, transmission, and storage of such data. Some works in this field present measurement systems using of-the-shelf sensors and actuators. This paper aims to check the effectiveness, ease, and robustness of the AD8232 cardiac sensor for its use in telemedicine. Twenty experiments were performed using different devices and sensors and the results show that although it is an efficient sensor for studying or practicing with micro-controllers and sensors, it is not an effective solution for professional use. It presents problems with the position of the electrodes and the sensitivity of the sensor. Also, the device creates noise signals (impairing the collection of data), doesn’t allow the control of multiple parameters, and has limitations in technology. Most of the graphs made by the AD8232 module did not form curves that would allow their interpretation. The conclusion, considering the difficulty in obtaining good graphics, is that this sensor cannot be applied professionally.